Reduction of selected pathogenic bacteria in steamed green mussel (Perna viridis) - Gamez, Clarence P.
The green mussel (Perna viridis) is an important part of human diet as it provides a high quality of source of protein. Consumption of this green mussel can pose health risk to the consumers as they are filter feeders that obtain nutrients by pumping large quantities of water, thus have the capability of accumulating harmful microorganisms that are pathogenic to humans. Steaming has been applied to the green mussel with treatments 100°C-6 min, 100°C-4min, 100°C-2 min, 90°C-6 min, 90°C-4 min, 90°C-2 min, 80°C-6 min, 80°C-4 min, and 80°C-2 min. The steamed samples were subjected to microbial analysis (Total Plate Count, test for Salmonella, Vibrio parahaemolyticus, Vibrio cholera and Escherichia coli) and the results obtained were compared to the results of the microbial analysis of the raw sample. Significant decrease in the microbial content of the green mussel has been observed after steaming. High level of bacteria has been reduced especially on treatment 100°C-6 min that the microbial load has totally reached 0 in count.